Information Technology Based Project Management: Critical Success Factors and Indicators of Success - Shinta Winasis; Kevin Harlis; Jaka Pradana (Dinasti International Journal of Digital Business Management, 2024)
In the business world that is increasingly moving towards digitalization, technology-based project management is a branch of management that is gaining more attention, in line with the increasing growth of startup companies and the digital transformation process of companies. Looking back at the failure rate of information technology-based projects in the past, it can be concluded that project failure not only causes financial losses but can also impact the reputation and trust of clients, so it is important to be equipped with good project management skills. Management needs to learn the knowledge and have the skills to manage information technology projects in order to increase the chances of success. This paper will discuss project management based on information systems, including critical success factors and indicators of success. The research was conducted by reviewing the literature. From the research results, it is concluded that the critical success factors for information technology-based project management are budget, methodology, technical competence of the team and risk management along with adequate mitigation measures and adaptability to sudden changes and state of the art innovation. The indicators of project success are based on the benefits of the product produced, product quality, sustainability and ROI.